The influence of workplace stress and coping on depressive symptoms among registered nurses in Bangladesh - Reva Mondal; Yajai Sitthimongkol; Nopporn Vongsirimas; Natkamol Chansatitporn; Kathy Hegadoren (Belitung Raya Foundation, Indonesia, 2022)
Background: Nurses report high levels of workplace stress, which has been linked to an increased risk for experiencing depressive symptoms.Nurses’ workplace stress is also linked to increased absenteeism and decreased job satisfaction. Objectives: The objectives of this study were to examine: (1) the incidence of depressive symptoms among hospital-based registered nurses in Bangladesh; (2) common sources of workplace stress and their relationships to individual characteristics and depressive symptom scores; and (3) the potential mediating roles of coping strategies in the relationship between workplace stress and depressive symptoms. Methods: A cross-sectional study design involved three hundred and fifty-two registered nurses. Data were collected using a demographic questionnaire and three standardized tools measuring sources of nurses’ workplace stress, coping strategies, and depressive symptoms. Results: More than half of the participants scored ≥ 16 on the CES-D, which was associated with a major depression episode. Total NSS scores had a small but significant influence on scores on the depression scale. Coping strategies had no mediated effect on the relationship between workplace stress and scores on the depression scale. Low-reliability coefficients for subscales of two of the standardized tools highlight the challenge for researchers in developing countries to address contextual differences that may influence the meanings attached to individual items. Conclusion: Findings suggest that the mental health of registered nurses in Bangladesh requires immediate attention in part by attending to workplace stressors. Further research should focus on a deeper understanding of Bangladeshi registered nurses’ work experiences and the unique contribution that workplace stressors have on their physical and mental health.